Regional Variations in Stillbirth and Relation Between Extramarital Birth and Stillbirth in Bulgaria - Dima Tsanova; Toni Vekov (Journal of Biomedical & Clinical Research, 2018)
Stillbirth rate is an essential indicator of population health and is much more common than presumed. In 2014, it was 7.34‰ in Bulgaria. These trends are seen against the background of a continuous process of increasing proportion of births to unmarried women. This report aims to investigateand conduct a comparative analysis of indicators of stillbirth and extramarital births in Bulgaria for a 15-year period. The data was derived from the National Statistical Institute (NSI) and Eurostat and statistically processed with Statistical Package for Social Science version 24.0 (SPSS v.24.0). The correlation coefficient of Pearson was used to establish the relationship between stillbirth rates and extramarital births.Despite the technological progress of contemporary medicine, the stillbirth rate in Bulgaria during the last 15 years remained almost the same – from 7.48‰ in 2000 to 7.34‰ in 2014. One of the factors that may increase the risk for stillbirth is the marital status of the mother. The proportion of extramarital stillbirths for the country was 74.70% of all stillbirths for 2014, but in several districts, this proportion was 100%. Extramarital births and stillbirth rate in Bulgaria seem to be related. There are persisting regional differences in Bulgaria. A potential explanation includes health inequalities and welfare differences.